Nouvelle interprétation du bâtiment méroïtique XLIII de Meinarti (Nubie soudanaise) : Quelques pistes de réflexion pour distinguer entrepôts, greniers et marchés - Choimet, Gabrielle (Études et Travaux, 2024)
Building XLIII at Meinarti was initially interpreted as a warehouse, before being eventually attributed to a market. However, the presence of a raised floor and pairs of interconnecting rooms could not be satisfactorily explained. Although its function as a public facility is not questioned, Building XLIII raises issues as to the exact nature of the activities performed within its walls. A closer examination of the archaeological data shows that its interpretation as a marketplace with underground storage spaces is not consistent with the size of the low vaulted cellars underneath each room. Our hypothesis is that the raised floor rather acts as insulation against rising damp, which is perfectly conceivable in the context of food storage (cereals, wine, other types of foodstuffs). Interestingly, the closest parallels to this unique type of crawl space are found in the Western Roman world.